The Definitive Guide to Django Web Development Done Right - Holovaty, Adrian. (Apress, 2009)
This latest edition of The Definitive Guide to Django is updated for Django 1.1, and, with the forwardcompatibility guarantee that Django now provides, should serve as the ultimate tutorial and reference for this popular framework for years to come. Django, the Pythonbased equivalent to Rubys Rails web development framework, is one of the hottest topics in web development today. Lead developer Jacob KaplanMoss and Django creator Adrian Holovaty show you how they use this framework to create awardwinning web sites by guiding you through the creation of a web application reminiscent of ChicagoCrime.org. The Definitive Guide to Django is broken into three parts, with the first introducing Django fundamentals such as installation and configuration, and creating the components that together power a Djangodriven web site. The second part delves into the more sophisticated features of Django, including outputting nonHTML content such as RSS feeds and PDFs, caching, and user management. The appendixes serve as a detailed reference to Djangos many configuration options and commands.